2015
DOI: 10.1164/rccm.201502-0383oc
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypoxemia Severity and Renin–Angiotensin System Activity in Obstructive Sleep Apnea

Abstract: The severity of nocturnal hypoxemia influences the magnitude of renal, but not the systemic, RAS activation independently of obesity in patients with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 45 publications
2
47
1
Order By: Relevance
“…292 In addition, intermittent hypoxia induces the sympathetic nervous system to increase vascular resistance, downregulates expression of the kallikrein-kallistatin vasodilator Shelley Transforming growth factor β inhibition 446 Pro-fibrotic metalloproteinase inhibition 447 Anti-fibrotic metalloproteinase activation 447 Destabilization of renal Remote ischemic pre-conditioning [384][385][386][387][388][389][390] hypoxia-inducible factor Prolyl hydroxylase inhibition 244,448 von Hippel-Lindau protein inhibition 449 pathway, and activates the renal renin-angiotensin-aldosterone system to cause vasoconstriction. [293][294][295][296][297][298][299] Together these processes conspire to produce renal fibrosis and sustained hypertension and their associated means of reducing renal oxygenation ( figure 1). 82,[300][301][302][303][304] Oxygenation is further compromised by nocturnal hypoxia altering parasympathetic control of heart rate and inducing left ventricular hypertrophy.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…292 In addition, intermittent hypoxia induces the sympathetic nervous system to increase vascular resistance, downregulates expression of the kallikrein-kallistatin vasodilator Shelley Transforming growth factor β inhibition 446 Pro-fibrotic metalloproteinase inhibition 447 Anti-fibrotic metalloproteinase activation 447 Destabilization of renal Remote ischemic pre-conditioning [384][385][386][387][388][389][390] hypoxia-inducible factor Prolyl hydroxylase inhibition 244,448 von Hippel-Lindau protein inhibition 449 pathway, and activates the renal renin-angiotensin-aldosterone system to cause vasoconstriction. [293][294][295][296][297][298][299] Together these processes conspire to produce renal fibrosis and sustained hypertension and their associated means of reducing renal oxygenation ( figure 1). 82,[300][301][302][303][304] Oxygenation is further compromised by nocturnal hypoxia altering parasympathetic control of heart rate and inducing left ventricular hypertrophy.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…Recently, reduced renovascular sensitivity in response to a 60-minute angiotensin II infusion was observed in OSA patients with severe nocturnal hypoxemia when compared with milder OSA patients and non-apneic, obese controls (97). No changes were observed in BP or in circulating markers of RAS activation, suggesting a specific direct impact of IH on the kidney.…”
Section: Osa As a Causative Factor In Ckdmentioning
confidence: 99%
“…Obstructive sleep apnea and chronic kidney disease: open questions on a potential public health problem were already observed in mild-moderate OSA (23), severe hypoxemia was associated with worse hemodynamic and functional renal impairment (17,25).…”
Section: Editorialmentioning
confidence: 99%
“…Conversely, other studies reporting no effect of hypoxemia mainly included subjects with mild respiratory disorders and desaturations (8). One experimental study in humans demonstrated that the more severe hypoxemia, the greater the activation of the RAS and, therefore, the more likely a renal impairment (25). Longitudinal studies used a threshold of 12% night time with SaO 2 <90% as cut-off to separate patients with and without accelerated eGFR decline (10).…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation